Sharing Economy - Chancen und Risiken aus ökonomischer Sicht - Aykanat, Cengiz

Heterogeneity in Contests, Sources and Implicants - Suvorina, Tatiana

An Automated Solar-Biomass Hybrid Dryer System for Rural Communities in Ghana - Obeng-Akrofi, George; Oppong Akowuah, Joseph; Opoku-Agyemang, Gifty; Nkrumah, Isaac; Donkor, Micheal K. E.; Tamakloe, Reuben Y.; Ampong, Francis K.; Klaus, Tobias; Krauter, Stefan; Waldhoff, Maike; Olenberg, Alexander; Kenig, Eugeny (Proceedings of SWC2017/SHC2017)

Decision Support for the Optimal Coordination of Spontaneous Volunteers in Disaster Relief - Rauchecker, Gerhard; Schryen, Guido (Proceedings of the 15th International Conference on Information Systems for Crisis Response and Management)
When responding to natural disasters, professional relief units are often supported by many volunteers which are not affiliated to humanitarian organizations. The effective coordination of these volunteers is crucial to leverage their capabilities and to avoid conflicts with professional relief units. In this paper, we empirically identify key requirements that professional relief units pose on this coordination. Based on these requirements, we suggest a decision model. We computationally solve a real-world instance of the model and empirically validate the computed solution in interviews with practitioners. Our results show that the suggested model allows for solving volunteer coordination tasks of realistic size near-optimally within short time, with the determined solution being well accepted by practitioners. We also describe in this article how the suggested decision support model is integrated in the volunteer coordination system which we develop in joint cooperation with a disaster management authority and a software development company.
Keywords: Coordination of spontaneous volunteers; volunteer coordination system; decision support; scheduling optimization model; linear programming

Classifying the Ideational Impact of IS Review Articles: A Natural Language Processing Based Approach - Prester, Julian; Wagner, Gerit; Schryen, Guido (Proceedings of the 2018 International Conference on Information Systems (ICIS 2018))

Ranking of Classification Algorithms in AutoML - Graf, Helena

Anschlüsse eröffnen, Entwicklungen ermöglichen. Qualifizierungsbausteine inklusiv in einer dualisierten Ausbildungsvorbereitung. Reflexionen und Ergebnisse aus dem Forschungs- und Entwicklungsprojekt QBi

Hinführung zum Projekt - Anschlüsse eröffnen, Entwicklungen ermöglichen - Qualifizierungsbausteine in einer dualisierten Ausbildungsvorbereitung - Frehe-Halliwell, Petra; Kimmelmann, Nicole; Kremer, H.-Hugo; Peitz, Nina-Madeleine; Sloane, Peter F. E.; Volgmann, Simone (Anschlüsse eröffnen, Entwicklungen ermöglichen. Qualifizierungsbausteine inklusiv in einer dualisierten Ausbildungsvorbereitung. Reflexionen und Ergebnisse aus dem Forschungs- und Entwicklungsprojekt QBi.)

Qualifizierungsbausteine vor Ort - Entwicklung, Darstellung und Zusammenführung der Standortkonzepte - Frehe-Halliwell, Petra; Kremer, H.-Hugo (Anschlüsse eröffnen, Entwicklungen ermöglichen. Qualifizierungsbausteine inklusiv in einer dualisierten Ausbildungsvorbereitung. Reflexionen und Ergebnisse aus dem Forschungs- und Entwicklungsprojekt QBi.)

Ausblick: Zur didaktischen Gestaltung der Ausbildungsvorbereitung - Frehe-Halliwell, Petra; Kremer, H.-Hugo (Anschlüsse eröffnen, Entwicklungen ermöglichen. Qualifizierungsbausteine inklusiv in einer dualisierten Ausbildungsvorbereitung. Reflexionen und Ergebnisse aus dem Forschungs- und Entwicklungsprojekt QBi.)

Didaktik der Ausbildungsvorbereitung als (eine) Didaktik beruflicher Bildung? - Frehe, Petra; Kremer, H.-Hugo (Didaktik der beruflichen Bildung - Selbstverständnis, Zukunftsperspektiven und Innovationsschwerpunkte)

Professionalisierung der Studieneingangsphase - Peer Mentoring an der Fakultät für Wirtschaftswissenschaften - Sloane, Hannah; Kremer, H.-Hugo (Heterogenität als Chance. Bilanz und Perspektiven des Qualitätspakt Lehre-Projekts an der Universität Paderborn)

Exzellenzprogramm der Fakultät für Wirtschaftswissenschaften. Hintergrund, Ausrichtung und Elemente des Programms - Kremer, H.-Hugo; Rüsing, Peter (Heterogenität als Chance. Bilanz und Perspektiven des Qualitätspakt Lehre-Projekts an der Universität Paderborn)

Description Languages for Consistency Management Scenarios Based on Examples from the Industry Automation Domain - Anjorin, Anthony; Yigitbas, Enes; Leblebici, Erhan; Schürr, Andy; Lauder, Marius; Witte, Martin (Programming Journal)

Test Case Migration: A Reference Process Model and its Instantiation in an Industrial Context - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan (Joint Proceedings of the Workshops at Modellierung 2018 co-located with Modellierung 2018, Braunschweig, Germany, February 21, 2018.)

Bidirectional Method Patterns for Language Editor Migration - Yigitbas, Enes; Anjorin, Anthony; Leblebici, Erhan; Grieger, Marvin (Modelling Foundations and Applications - 14th European Conference, ECMFA 2018, Held as Part of STAF 2018, Toulouse, France, June 26-28, 2018, Proceedings)

On the development of consistent user interfaces (extended abstract) - Anjorin, Anthony; Yigitbas, Enes; Kaindl, Hermann; Popp, Roman (Conference Companion of the 2nd International Conference on Art, Science, and Engineering of Programming, Nice, France, April 09-12, 2018)

Who Guards the Guards? On the Validation of Test Case Migration - Jovanovikj, Ivan; Yigitbas, Enes; Anjorin, Anthony; Sauer, Stefan (Softwaretechnik-Trends, Proceedings of the 20th Workshop Software-Reengineering & Evolution (WSRE) & 9th Workshop Design for Future (DFF))

Model-based UI Modernization: From Legacy UIs to Self-adaptive UIs - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan (Softwaretechnik-Trends, Proceedings of the 20th Workshop Software-Reengineering & Evolution (WSRE) & 9th Workshop Design for Future (DFF))

Forming Tile Shapes with Simple Robots - Gmyr, Robert; Hinnenthal, Kristian; Kostitsyna, Irina; Kuhn, Fabian; Rudolph, Dorian; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 24th International Conference on DNA Computing and Molecular Programming)

What Makes Cooperatives Successful? Identifying the Determinants of Their Organizational Performance - Fanasch, Patrizia; Frick, Bernd (Journal of Wine Economics)

Information Flow Certificates - Töws, Manuel; Wehrheim, Heike (Theoretical Aspects of Computing – ICTAC 2018)
Information flow analysis investigates the flow of data in applications, checking in particular for flows from private sources to public sinks. Flow- and path-sensitive analyses are, however, often too costly to be performed every time a security-critical application is run. In this paper, we propose a variant of proof carrying code for information flow security. To this end, we develop information flow (IF) certificates which get attached to programs as well as a method for IF certificate validation. We prove soundness of our technique, i.e., show it to be tamper-free. The technique is implemented within the program analysis tool CPAchecker. Our experiments confirm that the use of certificates pays off for costly analysis runs.

Adapt Cases 4 BPM - A Modeling Framework for Process Flexibility in IIoT - Engels, Gregor; Strothmann, Thim Frederik; Teetz, Alexander (2018 IEEE 22nd International Enterprise Distributed Object Computing Workshop (EDOCW))

Das Blended Mentoring Concept: Digital gestützte Begleitung von Jugendlichen im Betriebspraktikum (Teil 1) - Gockel, C.; Kremer, H.-Hugo (Wirtschaft und Erziehung)

Das Blended Mentoring Concept: Digital gestützte Begleitung von Jugendlichen im Betriebspraktikum (Teil 2) - Gockel, C.; Kremer, H.-Hugo (Wirtschaft und Erziehung)

Tolerant consistency management in model-driven engineering - Weidmann, Nils (Proceedings of the 21st ACM/IEEE International Conference on Model Driven Engineering Languages and Systems Companion Proceedings - MODELS '18)

Provably Anonymous Communication Based on Trusted Execution Environments - Blömer, Johannes; Bobolz, Jan; Scheideler, Christian; Setzer, Alexander
In this paper, we investigate the use of trusted execution environments (TEEs, such as Intel's SGX) for an anonymous communication infrastructure over untrusted networks. For this, we present the general idea of exploiting trusted execution environments for the purpose of anonymous communication, including a continuous-time security framework that models strong anonymity guarantees in the presence of an adversary that observes all network traffic and can adaptively corrupt a constant fraction of participating nodes. In our framework, a participating node can generate a number of unlinkable pseudonyms. Messages are sent from and to pseudonyms, allowing both senders and receivers of messages to remain anonymous. We introduce a concrete construction, which shows viability of our TEE-based approach to anonymous communication. The construction draws from techniques from cryptography and overlay networks. Our techniques are very general and can be used as a basis for future constructions with similar goals.

Real-time Graph-Based 3D Reconstruction of Sparse Feature Environments for Mobile Robot Applications - Gaspers, Daniel; Knorr, Christoph; Nickchen, Tobias; Nickchen, Daniel; Mertsching, Barbel; Mohamed, Mahmoud A. (2018 IEEE International Symposium on Safety, Security, and Rescue Robotics (SSRR))

Short Digital Signatures and ID-KEMs via Truncation Collision Resistance - Jager, Tibor; Kurek, Rafael (Advances in Cryptology - ASIACRYPT 2018 - 24th International Conference on the Theory and Application of Cryptology and Information Security, Brisbane, QLD, Australia, December 2-6, 2018, Proceedings, Part II)

Simple and More Efficient PRFs with Tight Security from LWE and Matrix-DDH - Jager, Tibor; Kurek, Rafael; Pan, Jiaxin (Advances in Cryptology - ASIACRYPT 2018 - 24th International Conference on the Theory and Application of Cryptology and Information Security, Brisbane, QLD, Australia, December 2-6, 2018, Proceedings, Part III)

Drafting a Data Science Curriculum for Secondary Schools - Heinemann, Birte; Opel, Simone; Budde, Lea; Schulte, Carsten; Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Wassong, Thomas (Proceedings of the 18th Koli Calling International Conference on Computing Education Research - Koli Calling '18)
Keywords: Curriculum Development; Data Science; Secondary Sc; acm reference format; big data; curriculum development; data literacy; data science; educa-; interdisciplinary; secondary schools; tion

Multichannel vectorial holographic display and encryption - Zhao, Ruizhe; Sain, Basudeb; Wei, Qunshuo; Tang, Chengchun; Li, Xiaowei; Weiss, Thomas; Huang, Lingling; Wang, Yongtian; Zentgraf, Thomas (Light: Science & Applications)

Learning about learning curves from dataset properties - Scheibl, Manuel

Reduzierung des Energieverlustes im Smart Grid mittels Koalitionsbildung - Koch, Alexander

Multilamellar Vesicle Formation Probed by Rheo-NMR and Rheo-SALS under Large Amplitude Oscillatory Shear - Kuczera, Stefan; Gentile, Luigi; Brox, Timothy I.; Olsson, Ulf; Schmidt, Claudia; Galvosas, Petrik (Langmuir)

Multiprofessionelle Teams zur inklusiven Bildungsarbeit. Empirische Explorationen, theoretisch-konzeptionelle Annäherungen und praktische Gestaltung - Kückmann, Marie-Ann; Kremer, H.-Hugo (Vielfalt des Lernens im Rahmen berufsbezogener Standards)

Preface - Scheideler, Christian (Theor. Comput. Sci.)

Relays: Towards a Link Layer for Robust and Secure Fog Computing - Scheideler, Christian (Proceedings of the 2018 Workshop on Theory and Practice for Integrated Cloud, Fog and Edge Computing Paradigms, TOPIC@PODC 2018, Egham, United Kingdom, July 27, 2018)

Shape Recognition by a Finite Automaton Robot - Gmyr, Robert; Hinnenthal, Kristian; Kostitsyna, Irina; Kuhn, Fabian; Rudolph, Dorian; Scheideler, Christian (43rd International Symposium on Mathematical Foundations of Computer Science, MFCS 2018, August 27-31, 2018, Liverpool, UK)

Understand your chains and keep your deadlines: Introducing time-constrained profiling for NFV - Peuster, Manuel; Karl, Holger (IEEE/IFIP 14th International Conference on Network and Service Management (CNSM))

Stuck on a plateau? A model-based approach to fundamental issues in visual temporal-order judgments - Tünnermann, Jan; Scharlau, Ingrid (Vision)

Security in Highly Connected IT Systems – Results of the Bavarian Research Alliance FORSEC - Schillinger, Rolf; Schryen, Guido

Are Gift Purchases an Effective Driver of Customer Loyalty? - Eggert, Andreas; Steinhoff, Lena; Witte, Carina

Usability Evaluation of Model-Driven Cross-Device Web User Interfaces - Yigitbas, Enes; Anjorin, Anthony; Jovanovikj, Ivan; Kern, Thomas; Sauer, Stefan; Engels, Gregor (Proceedings of the 7th International Working Conference on Human-Centered Software Engineering (HCSE'18))

Studiengangsmanagement an der Fakultät für Wirtschaftswissenschaften. Organisation, Arbeitsgebiete und Herausforderungen - Kremer, H.-Hugo; Emmighausen, Laura; Mauer, Eileen (Heterogenität als Chance. Bilanz und Perspektiven des Qualitätspakt Lehre-Projekts an der Universität Paderborn)

Forschendes Lernen in der Informatik - In praxisnaher Projektgruppe einen Softwareentwicklungsprozess erforschen - Senft, Björn; Oberthür, Simon; Fischer, Holger Gerhard (Schriften zur allgemeinen Hochschuldidaktik - Band 3. Tagungsband Forschendes Lernen - The wider view)

Assist Users to Straightaway Suggest and Describe Experienced Problems - Senft, Björn; Fischer, Holger Gerhard; Oberthür, Simon; Patkar, Nitish (Design, User Experience, and Usability: Theory and Practice)

A Canvas Method to Foster Interdisciplinary Discussions on Digital Assistance Systems - Fischer, Holger Gerhard; Senft, Björn; Rittmeier, Florian; Sauer, Stefan (Design, User Experience, and Usability: Theory and Practice. Proceedings of the 20th International Conference on Human-Computer Interaktion (HCI International 2018))

Scheduling Shared Continuous Resources on Many-Cores - Althaus, Ernst; Brinkmann, Andre; Kling, Peter; Meyer auf der Heide, Friedhelm; Nagel, Lars; Riechers, Sören; Sgall, Jiri; Suess, Tim (Journal of Scheduling)

Preference-Based Reinforcement Learning Using Dyad Ranking - Schäfer, Dirk; Hüllermeier, Eyke (Discovery Science)